The impact of extended defects on the generation and recombination lifetime in n type In.53Ga.47As. (12th September 2019) - Hsu, Po-Chun (Brent); Simoen, Eddy; Merckling, Clement; Eneman, Geert; Mols, Yves; Han, Han; Alian, AliReza; Collaert, Nadine; Heyns, Marc
Abstract: The relationship between the threading dislocation density (TDD), the generation ( τ g ) and recombination lifetime ( τ r ) in relaxed n-type In.53 Ga.47 As is investigated for a series of p+n junction diodes, containing a TDD ranging from 10 5 to 10 10 cm −2 . The TDs are generated intentionally by lattice-misfit growth on semi-insulating (SI) InP and GaAs substrates. The lifetimes have been extracted from diode current–voltage ( I – V ) and photoluminescence (PL) analysis showing that TDDs affect their values above a density of about 1  ×  10 7 cm −2 ( τ g, E ~ 0 ) and about 1  ×  10 8 cm −2 ( τ r and τ PL ), which can be well-explained by the charged dislocation cylinder model. In addition, a detailed comparison between the results from deep level transient spectroscopy and from the diode characterization is performed, showing that the responsible G / R center shifts toward mid-gap in In.53 Ga.47 As and transfers from a native point defect (PD1) to a TD (E2/H1). Finally, the classical concept of generation lifetime and recombination lifetime in terms of dislocations is discussed based on the results.